School of Spectator, Theater as Extension and Citizenship. - Vieira Falabella, Márcia Cristina; de Jesus, Messias Matheus (Guará Journal, 2019)
This work intends to bring some reflections on the experience of the extension project School of Spectator executed in a partnership between the Federal University of Juiz de Fora and the Center of Theater Studies - Grupo Divulgação. In its 32 years of operation, the project takes schools, centers and communities to the Theater, contributing to the formation of spectators of working classes. We will make a brief analysis of the participation of the centers attended by the project during the celebrations of the 50 years of Grupo Divulgação, which happened in the first semester of 2016. Student participation was observed during the presentations and their views on the performances. The social themes presented on stage are deepened in the classroom, through pedagogical activities developed by students and teachers. The results are positive and point to the contribution of theater to the construction of citizenship.